Social media marketing for dummies - Singh, Shiv; Diamond, Stephanie (--For dummies., 2015)
"Social media marketing is a fast, affordable, and effective way to reach your customers - but it's competitive and always evolving. This friendly guide distills the core concpets, trends, and recommendations down to bite-sized nuggets, giving you expert and approachable guidance on using social media to maintain your rep as a marketing maven."--Back cover.